2002
DOI: 10.1093/chemse/27.8.691
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Odorant-binding Protein Selectively Binds to a Human Olfactory Receptor

Abstract: Odorant-binding proteins (OBPs) represent a highly abundant class of proteins secreted in the nasal mucus by the olfactory neuroepithelium. These proteins display binding affinity for a variety of odorant molecules, thereby assuming the role of carrier during olfactory perception. However, no specific interaction between OBP and olfactory receptors (ORs) has yet been shown and early events in olfaction remain so far poorly understood at a molecular level. Two human ORs, OR 17-209 and OR 17-210, were fused to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…This does not mean that porcine OBPs only bind to olfactory receptors originating from same species. In contrast to our results, an interaction between the human olfactory receptor and the porcine OBP has been reported [25]. These above results also indirectly indicate that OBPs can bind to various different odorants and also support the results from previous studies, where OBPs were shown to bind to a variety of volatile compounds [5,26,27].…”
Section: Discussionsupporting
confidence: 86%
“…This does not mean that porcine OBPs only bind to olfactory receptors originating from same species. In contrast to our results, an interaction between the human olfactory receptor and the porcine OBP has been reported [25]. These above results also indirectly indicate that OBPs can bind to various different odorants and also support the results from previous studies, where OBPs were shown to bind to a variety of volatile compounds [5,26,27].…”
Section: Discussionsupporting
confidence: 86%
“…Whether or not the ligand-linked alterations of OBP dynamics seen in this study are sufficient to allow recognition of the ligation state of OBPs by the olfactory receptor remains to be seen. In any event, the presence of such conformational modifications provide additional, unforeseen elements which may enrich potential chemoreception mechanisms such as those proposed by Matarazzo et al (19).…”
Section: Discussionmentioning
confidence: 92%
“…The primary approach is experimental, where excitatory responses are identified following the exposure of olfactory receptor neurons (one receptor corresponds to one neuron) to a panel of odorants. [9][10][11][12] Excitatory responses that arise from these interactions over a range of concentrations of odorants (typically organic chemical compounds) are then measured. This opinion paper is primarily concerned with the secondarycomputational-approach.…”
Section: Opinionmentioning
confidence: 99%
“…Functional studies have established this odorant as strongly excitatory for the hOR17-209 receptor. 12 The figures represent the simulation box that is used for our molecular dynamics simulations. This box consists of a model of the receptor in yellow.…”
Section: Re-addressing the Or-odorant Interaction Paradigmmentioning
confidence: 99%